Efficient Synthesis of Amines by Iron‐Catalyzed C=N Transfer Hydrogenation and C=O Reductive Amination. Issue 6 (12th January 2018) - Facchini, Sofia Vailati; Cettolin, Mattia; Bai, Xishan; Casamassima, Giuseppe; Pignataro, Luca; Gennari, Cesare; Piarulli, Umberto
Abstract: Here we report the catalytic transfer hydrogenation (CTH) of non‐activated imines promoted by a Fe‐catalyst in the absence of Lewis acid co‐catalysts. Use of the (cyclopentadienone)iron complex1, which is much more active than the classical 'Knölker complex'2, allowed to reduce a number of N‐aryl and N‐alkyl imines in very good yields using i PrOH as hydrogen source. The reaction proceeds with relatively low catalyst loading (0.5–2 mol%) and, remarkably, its scope includes also ketimines, whose reduction with a Fe‐complex as the only catalyst has little precedents. Based on this methodology, we developed a one‐pot CTH protocol for the reductive amination of aldehydes/ketones, which provides access to secondary amines in high yield without the need to isolate imine intermediates. Abstract :